Taxation and Income Inequality in ASEAN Countries - Angga Alexander; Beta Yulianita Gitaharie (ETIKONOMI, 2024)
Research Originality: This study contributes to literature by investigating the impact of taxation on income inequality, with a specific focus on Southeast Asian countries.Research Objectives: To investigate the impact of taxation on income inequality in Association of Southeast Asian Nations (ASEAN) countries.Research Methods: A panel data model focusing on ASEAN from 1998 to 2021 was used, and a two-stage least squares (2SLS) estimation method, incorporating fixed effects and instrumental variables was used. Tax instrument comprised two components, namely tax ratio, reflecting volume of tax; and tax structure, representing direct, indirect, and income taxes.Empirical Results: The results showed that tax ratio, direct tax, and income tax reduced income inequality in Southeast Asia. However, the magnitude of the impact should be more significant. Prioritizing education and improving the quality of workforce could effectively reduce income inequality, as shown by Singapore's success in this area.Implications: This study had significant implications for ASEAN policymakers, as it offered valuable insights into designing and implementing taxation policies to reduce income inequality and promote economic development across the region. JEL Classification: D63, H20, H23How to Cite:Alexander, A., Gitaharie, B. Y. (2024). Taxation and Income Inequality in ASEAN Countries. Etikonomi, 23(1), 397 – 414. https://doi.org/10.15408/etk.v23i2.32352.